KONSELING MEMENGARUHI PERUBAHAN PERILAKU CALON AKSEPTOR DALAM PEMILIHAN ALAT KONTRASEPSI IUD - Desfauza, Evi; Ginting, Idau; Elizawarda, Elizawarda (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2013)
Indonesia is a large population of about 215 million people, the fourth largest in the world with quality is still very low, ranks 112 out of 175 in 2003. In 2005 Indonesia's population increased from 219.9 million to 231.3 million in 2009 with a population growth rate of 1.29% per year. Based on the 2002-2003 IDHS, that TFR Popinsi North Sumatra in the position of numbers: 3, achieving an active participant KB 2006 was 1.187.815 or 62.06% of the EFA: 1914002, and tends hormonal contraceptive options, the pill: 35.37%, 33.15% whereas injections IUD only 11.63%. The research design using design methods Quasi Experiments with one group before and after intervention. The population is all couples of childbearing age is recorded in the clinis as many as 4,241 people Tuntungan Medan. Sample of 79 people, sampling the accidental sampling all potential acceptors from June to October 2012. Analysis of univariate and bivariate implemented using computer software. The results are significant differences between the behavior before and after counseling about family planning contraceptive IUD is an average increase of knowledge 11:08, SD = 16.87. p-value = 0.00, mean increase Attitude 9899 with SD = 11.189. p=0.00, and an average increase of 2392 action with SD = 7,305, p = 0.005, Behavior change takes a along time and repeated information, it is expected to midwives and other health workers can provide counseling using the media / props repeatedly untul the patient make their own decisions with the rigth and need further research on husband.